Pośrednicy kulturowi i ich rola w gospodarce kreatywnej - Stachowiak, Krzysztof (Załącznik Kulturoznawczy, 2023)
The paper presents the role that cultural intermediaries play in creative economy. Cultural intermediaries are a specific and very important category of subjects in the creative economy. They play a key role especially in the dissemination of creative goods. They also serve as intermediaries between creators and producers. However, they are not only involved in connecting sellers with buyers, but are also involved in shaping the final value of goods. Therefore, cultural intermediaries can play a threefold role in the creative economy. They can be: (1) individuals or groups acting as a medium between cultures; (2) a collection of professions to transfer cultural values to society; (3) individuals or groups involved in the transfer of creative and cultural goods, cultural values between creators and audience